Infective complications of open-heart surgery and the monitoring of infections by the NBT test - Freeman, R. (1973)
Freeman, R., King, B., and Hambling, M. H. (1973).Thorax, 28, 617-621. Infective complications of open-heart surgery and the monitoring of infections by the NBT test. Seventy-four consecutive patients undergoing open-heart surgery were extensively investigated, preoperatively and postoperatively, for evidence of infection. The incidence of the infective complications encountered is presented, together with discussion on the aetiology of these complications. A previously unrecognized infective complication is described, this being a high incidence of infection with Mycoplasma pneumoniae. The series also reports an assessment of the nitroblue tetrazolium (NBT) test in these patients, and it is concluded that the system evolved in this series, of minimal chemoprophylaxis and constant monitoring of infection, affords a logical alternative to conventional methods using massive prophylaxis.